1997
DOI: 10.3758/bf03200595
|View full text |Cite
|
Sign up to set email alerts
|

Ratings for Welsh words and their English equivalents

Abstract: The rating of English words and their Welsh equivalents provided the opportunity to compare subjective ratings in two languages as well as the opportunity to compare ratings in a deep and a shallow orthography (English and Welsh, respectively). Four variables-age of acquisition (AOA),familiarity, concreteness, and imageability-were rated. AOAand imageability emerged as the two most important extralingual variables (r = .8 and.73, respectively). Although the patterns of ratings were generally consistent within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The easy and hard categories had equal numbers of 4–7 letter words. In addition the average meaningfulness (easy = 6.66, hard = 6.61), imageability (easy = 6.18, hard = 6.36) and concreteness (easy = 6.08, hard = 6.46) were similar across the easy and hard categories according to the word ratings from Paivio, Yuille, and Madigan [24] and Fear [25].…”
Section: Methodsmentioning
confidence: 90%
“…The easy and hard categories had equal numbers of 4–7 letter words. In addition the average meaningfulness (easy = 6.66, hard = 6.61), imageability (easy = 6.18, hard = 6.36) and concreteness (easy = 6.08, hard = 6.46) were similar across the easy and hard categories according to the word ratings from Paivio, Yuille, and Madigan [24] and Fear [25].…”
Section: Methodsmentioning
confidence: 90%
“…Because it was considered of paramount importance that the English and Welsh words were of equal familiarity, the words used in the Welsh list were translations of the words used in the English list. Fear (1997) has shown that familiarity ratings for English words and their Welsh translations are highly correlated. The order of the words on the Welsh list was the same as the order of their translations on the English list.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to Gilhooly and Logie (1980a), published AoA norms exist for English (Bird, Franklin, & Howard, 2001; Carroll & White, 1973a; Fear, 1997; Gilhooly & Hay, 1977; Gilhooly & Logie, 1980b; Masterson & Druks, 1998; Stratton, Jacobus, & Brinley, 1975), as well as Spanish (Cuetos, Ellis, & Alvarez, 1999; see also Piñeiro & Manzano, 2000, for AoA classification based on children's speech), French (Alario & Ferrand, 1999; Bonin, Peereman, Malardier, Meot, & Chalard, 2003), Welsh (Fear, 1997), Italian (Barca, Burani, & Arduino, 2002; Dell'Acqua, Lotto, & Job, 2000), Dutch (Ghyselinck, Custers, & Brysbaert, 2003; Ghyselinck, De Moor, & Brysbaert, 2000), and Icelandic (Pind, Jonsdottir, Gossurardottir, & Jonsson, 2000). There is also a new online source of AoA ratings for pictures of objects and actions for seven languages (Szekely et al, 2004).…”
Section: The Measurement Of Aoa and Other Psycholinguistic Variablesmentioning
confidence: 99%